2013
DOI: 10.1097/inf.0b013e31828ba08c
|View full text |Cite
|
Sign up to set email alerts
|

Does Respiratory Virus Coinfection Increases the Clinical Severity of Acute Respiratory Infection Among Children Infected With Respiratory Syncytial Virus?

Abstract: Non-RSV respiratory virus coinfection is not uncommon in RSV-infected children and may increase the severity of RSV disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
52
1
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(63 citation statements)
references
References 25 publications
7
52
1
3
Order By: Relevance
“…They explained that heightened immune response during a primary infection may discourage colonization by a second viral pathogen, leading to lowered prevalence of multiple viruses in young infants [20]. Double and triple viral co-infection represented (17.1% and 7.3% respectively), which is comparable to other studies that ranged (12-20%) regarding double co-infection and (1.1-3.9%) for triple infection [19,21,22]. RV was the most frequently detected virus in single and mixed viral infection.…”
Section: Discussionsupporting
confidence: 76%
See 2 more Smart Citations
“…They explained that heightened immune response during a primary infection may discourage colonization by a second viral pathogen, leading to lowered prevalence of multiple viruses in young infants [20]. Double and triple viral co-infection represented (17.1% and 7.3% respectively), which is comparable to other studies that ranged (12-20%) regarding double co-infection and (1.1-3.9%) for triple infection [19,21,22]. RV was the most frequently detected virus in single and mixed viral infection.…”
Section: Discussionsupporting
confidence: 76%
“…The discrepancy in proportion of viral agents may be due to differences in pathogen epidemiology, study populations, and/or the time the study was conducted due to seasonal variation. The leading combination in the current study was RV/AdV and RV/RSV, which was comparable to other studies [19,21,22]. Although RSV/ hMpV combination was reported by some studies [17,25,26], this combination was absent in our study and other studies [19,27].…”
Section: Respiratory Virussupporting
confidence: 38%
See 1 more Smart Citation
“…Although some studies have reported cases with these characteristics [5254], reports by other authors have suggested that co-infections are not synonymous with clinical differences or greater severity [5556]. …”
Section: Discussionmentioning
confidence: 99%
“…Conceptually, multiple pathogens should increase risk of severe illness; however, the inflammatory response generated by one virus may not be significantly increased by the presence of a second or third virus 8 . The published data regarding the outcomes associated with respiratory viral co-infection are mixed 14,15,2022 .…”
Section: Introductionmentioning
confidence: 99%